Humor in Workplace Leadership: A Systematic Search Scoping Review - Rosenberg, Caroline; Walker, Arlene; Leiter, Michael; Graffam, Joe (Frontiers in Psychology, 2021)
Humor studies are increasingly prevalent in workplace and leadership domains, it has shown significant development in the last 40 years. The multifaceted nature of humor means varied definitions and diverse measurement approaches have been approved. As a result, research methodologies and findings are not easily clarified, and have not been synthesized. The aim of this scoping review was to review the existing body of literature relevant to humor in workplace leadership to identify key research areas, methodologies used, guiding theoretical frameworks, and gaps that are persisting over the last 40 years. Using qualitative review methods, four key themes in the research emerged relating to: (1) humor styles and outcomes; (2) humor as communication and discursive resource; (3) variables in the humor and leadership relationship; and (4) cultural context. This review demonstrates significant research progress on the topic of humor in workplace leadership. Research progress and gaps are discussed based on five key questions. Future research directions are outlined and discussed.